Critical theory and social inequality - Rehbein, Boike (Tempo Social, 2018)
This paper argues that social inequality is possibly the core topic of any critical theory in the social sciences – for epistemological as well as ethical reasons. As the social scientist is part of the scientific object, namely society, the project of science is interdependent with its object. For this reason, the structure of society itself influences the shape of social science. At the same time, the processes and results of the scientific project have an impact on society. Science changes its own object. Epistemological issues are therefore tied to the ethical questions about the social organization of the scientific project, access to science, the structure of society and inequality. If access to science is unequal and if science contributes to inequality, this has to be legitimized scientifically.